Risk Evaluation of The Use of The Umbrella Contract for The Construction Project for Medium Voltage Distribution in South Surabaya Region Using The Expected Monetary Value - Irawan Dwi Purnomo; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2020)
In the program for accelerating the distribution of electricity to users, also known as the getting electricity program by PT. PLN Persero. Specifically, the distribution of the South Surabaya region has accelerated programs with vendors with a new contract system, namely the umbrella contract system. Where is based on the performance of the umbrella contract system in 2018 it has the potential risks that influence during the implementation process of this umbrella contract takes place. Using the stages of risk identification, risk assessment, and calculating the EMV (expected monetary value) analysis method to analyze each important risk event and its risk response. First, a preliminary survey was conducted to identify the risks that significantly influence the umbrella contract with the respondents who played an important role in the implementation of the umbrella contract. In the assessment of each risk, it is found that the risks that have an important influence during the umbrella contract process take place. Expected monetary value is used to analyze the contingency costs that need to be prepared from each risk variable based on the risk response or risk mitigation carried out during the implementation of the umbrella contract The result obtained in this study there are 4 risks need to be concern during implementation of umbrella agreement cause had great impact for the project cost.